2020
DOI: 10.1177/2050313x20929561
|View full text |Cite
|
Sign up to set email alerts
|

Successful rechallenge with paliperidone after clozapine treatment for a patient with dopamine supersensitivity psychosis

Abstract: We describe the case of a 49-year-old Japanese male patient successfully treated with a paliperidone rechallenge following 2-year treatment with clozapine for treatment-resistant schizophrenia. He had responded well to conventional antipsychotic treatment for the initial psychotic episode but gradually developed dopamine supersensitivity; even treatment with paliperidone and another antipsychotic medication (a total up to 1700 mg in chlorpromazine-equivalent dose) had not improved his psychotic symptoms. Cloza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It is ironic that the recent American Psychiatric Association recommendations for long-term antipsychotic use in patients with schizophrenia recommend switching to clozapine when patients stop improving on their initial antipsychotic medication, in that clozapine has been found to mitigate the molecular sensitivity reaction in the dopamine system aiDSP caused by the long-term use of antipsychotic medications, and also to reduce the long term mortality risk associated with all other antipsychotic medications. (American Psychiatric Association, 2020;Fava, 2020;Fedak, Bernal, Capshaw, & Gross, 2015;Kobayashi et al, 2020;Kose & Cetin, 2018;Oishi et al, 2018;Vermeulen, van Rooijen, van de Kerkhof, Sutterland, Correll, & de Haan, 2019).…”
mentioning
confidence: 99%
“…It is ironic that the recent American Psychiatric Association recommendations for long-term antipsychotic use in patients with schizophrenia recommend switching to clozapine when patients stop improving on their initial antipsychotic medication, in that clozapine has been found to mitigate the molecular sensitivity reaction in the dopamine system aiDSP caused by the long-term use of antipsychotic medications, and also to reduce the long term mortality risk associated with all other antipsychotic medications. (American Psychiatric Association, 2020;Fava, 2020;Fedak, Bernal, Capshaw, & Gross, 2015;Kobayashi et al, 2020;Kose & Cetin, 2018;Oishi et al, 2018;Vermeulen, van Rooijen, van de Kerkhof, Sutterland, Correll, & de Haan, 2019).…”
mentioning
confidence: 99%
“…2016 [12] RLAIs were more effective for patients with DSP (n = 61) than those without DSP (n = 33) in a 2-year observational study Blonanserin Tachibana et al, 2016 [13] Case series Niitsu et al, 2020 [14] This randomized controlled study showed that add-on treatment with both blonanserin (n = 26) and olanzapine (n = 29) similarly provided significant efficacy for DSP patients Paliperidone Kobayashi et al, 2020 [15] Case report Aripiprazole Tadokoro et al, 2017 [16] Case report Kanahara et al, 2018 [17] Case series showing that the introduction of aripiprazole following ECT successfully stabilized two patients with severe DSP Kanahara et al, 2020 [18] Case series from a clinical trial: A very-slow switching strategy to aripiprazole from other agents provided DSP patients with potential clinical stability and haloperidol 3 mg, respectively, for their first episodes of psychosis. A slight delusional mood remained for Patient 1, and her medication was subsequently switched to aripiprazole with a final dose-up to 30 mg.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the use of an LAI other than aripiprazole oncemonthly is a common strategy. Similarly, some oral antipsychotics with long half-lives such as blonanserin and paliperidone might be beneficial for patients with DSP [4] (Table 1: showing agents with efficacy for DSP [6][7][8][9][10][11][12][13][14][15][16][17][18]). However, both of the present patients showed persistent positive symptoms that were not controlled even by antipsychotic agents with long half-lives.…”
Section: Discussionmentioning
confidence: 99%